2019
DOI: 10.1186/s40425-019-0621-1
|View full text |Cite|
|
Sign up to set email alerts
|

Prognostic impact of immune gene expression signature and tumor infiltrating immune cells in localized clear cell renal cell carcinoma

Abstract: Background The tumor immune microenvironment has become the focus of research in clear cell renal cell carcinoma (ccRCC) due to its important role in immune surveillance post nephrectomy. This study investigates the correlation of tumor infiltrating immune cell characteristics with rates of recurrence following surgery in localized ccRCC. Methods We morphologically identified and scored tumor infiltrating lymphocytes (TILs) in hematoxylin and eosin (H&E) stained slides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
107
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(115 citation statements)
references
References 26 publications
8
107
0
Order By: Relevance
“…Immune infiltration in RCC has prognostic value, with influence in patient survival [77]. Again, the immune cell populations and their prognostic implications are subtype-specific; for instance, CD8+ T-lymphocyte infiltration associated with improved overall-survival in chRCC, while in pRCC a high infiltration by M1 macrophages associated with better patient outcome.…”
Section: The Connection Between Genetic Epigenetic and Immune Landsmentioning
confidence: 99%
“…Immune infiltration in RCC has prognostic value, with influence in patient survival [77]. Again, the immune cell populations and their prognostic implications are subtype-specific; for instance, CD8+ T-lymphocyte infiltration associated with improved overall-survival in chRCC, while in pRCC a high infiltration by M1 macrophages associated with better patient outcome.…”
Section: The Connection Between Genetic Epigenetic and Immune Landsmentioning
confidence: 99%
“…Since immune cell infiltration has been widely reported in ccRCC (3,(17)(18)(19)(20), the prognostic value of the immune-based markers has emerged. Prognostic models based on tumor-associated immune cells and genes have been developed (26)(27)(28). In this study, we pursued to expand the range of immune prognostic tools by exploring microenvironment component of ccRCC.…”
Section: Discussionmentioning
confidence: 99%
“…GO term analysis demonstrated that the majority of these DEGs were involved in the organization and regulation of the tumor microenvironment. It has been reported that the function of immune cells and extracellular matrix molecules are involved in the establishment of the tumor microenvironment of RCC (29).…”
Section: Discussionmentioning
confidence: 99%